Immunohistochemistry study of PHOX2B expression in Hirschsprung's disease allied disorders - Huan Wang; Xiulei Sun; Likun Yu; Yiyuan Xu (Elsevier, 2024)
Objective: This study aimed to investigate the significance of PHOX2B expression in Hirschsprung's disease allied disorders (HAD). Methods: Eight specimens of HAD were surgically resected and collected at Beijing Children's Hospital Affiliated to Capital Medical University Heilongjiang Hospital in recent years. Additionally, three specimens from patients with immature ganglion development in the intestinal wall and six control specimens from normal colons were also collected. PHOX2B, S-100, and CR antibodies were used for immunohistochemical staining to observe their expression at the mucosal, submucosal, and intrinsic muscular layer ganglia. Results: In the control group,the nuclei of the submucosal and myenteric ganglion cells showed strong or weak PHOX2B staining pattern,the mature ganglion cells showed weak PHOX2B staining,and the immature ganglion cells showed strong staining;S-100 only stained nerve fibers but not ganglion cells; CR stained nerve fibers in the mucosal layer and submucosal layer and also stained ganglion cells. These three antibodies showed different expression patterns in poorly developed enteric ganglia and immature enteric ganglion cells. Conclusion: PHOX2B is only expressed in the nucleus of ganglion cells, has discriminatory significance in identifying mature and immature ganglion cells, and is an essential marker for diagnosing HAD.